Rice residue burning trajectories in Eastern India: current realities, scenarios of change, and implications for air quality - Urban Cordeiro, Emily; Hamilton, Douglas S.; Rossiter, D.G.; Mahowald, Natalie; Hess, Peter; Malik, Ram; Singh, Ajoy; Samaddar, Arindam; McDonald, A.J. (IOP Publishing, 2024)
In 2019, the Government of India launched the National Clean Air Program to address the pervasive problem of poor air quality and the adverse effect on public health. Coordinated efforts to prevent agricultural burning of crop residues in Northwestern IGP (Indo-Gangetic Plain) have been implemented, but the practice is rapidly expanding into the populous Eastern IGP states, including Bihar, with uncertain consequences for regional air quality. This research has three objectives: (1) characterize historical rice residue burning trends since 2002 over space and time in Bihar State, (2) project future burning trajectories to 2050 under ‘business as usual’ and alternative scenarios of change, and (3) simulate air quality outcomes under each scenario to describe implications for public health. Six future burning scenarios were defined as maintenance of the ‘status quo’ fire extent, area expansion of burning at ‘business as usual’ rates, and a Northwest IGP analogue, of which both current rice yields and plausible yield intensification were considered for each case. The Community Earth System Model (CESM v2.1.0) was used to characterize the mid-century air quality impacts under each scenario. These analyses suggest that contemporary Bihar State burning levels contribute a small daily average proportion (8.1%) of the fine particle pollution load (i.e. PM2.5, particles ⩽2.5 μm) during the burning months, but up to as much as 62% on the worst of winter days in Bihar’s capital region. With a projected 142% ‘business as usual’ increase in burned area extent anticipated for 2050, Bihar’s capital region may experience the equivalent of 30 PM2.5 additional exceedance days, according to the WHO standard (24 h; exceedance level: 15 µg m−3), due to rice residue burning alone in the October to December period. If historical burning trends intensify and Bihar resembles the Northwest States of Punjab and Haryana by 2050, 46 d would exceed the WHO standard for PM2.5 in Bihar’s capital region.